Prawna ochrona tytułu zawodowego - Dobkowski, Jarosław (Studia Prawa Publicznego, 2022)
The study concerns the legal protection of professional titles, which are related to professional activities. It presents the genesis of such professional titles and their protection in Poland, which initially related to the protection of selected so-called ‘free legal professions’ (such as tax advisor, advocate, legal advisor, patent agent). The evolution of the subjective scope of how these professions occurred is also presented, including the introduction of this type of solution in relation to certain professions termed ‘free economic professions’ (chartered accountant, stockbroker and investment advisor), certain ‘free medical professions’ (nurse/nurse, midwife/midwife, laboratory diagnostician, physiotherapist, pharmacist), and selected socalled ‘free professions’, within which no professional self-governments functions (real estate appraiser). In this regard, it is noted that the legal protection of professional titles went beyond the scope of professional activity and also covered certain spheres of economic activity, an example of which are detective services provided by persons holding the professional title of detective. Against the background of the analysis of European standards, it is established here that the introduction of legal protection of professional titles should now be regarded as one of the means of regulating access to a profession. It is shown that the essence of the legal protection of the professional title comes down to the right of authorised persons to use the title on an exclusive basis, in order that other persons may not use the reserved title in this way, nor may their behaviour mislead the users of their services as to the fact that they hold a specific professional title, even if they have the appropriate knowledge and skills. There are various forms of legal protection – criminal, administrative and civil liability measures apply, but there are no comprehensive guarantees. A legally protected professional title can also be regarded as one of the determinants of the concept of a profession.